Methodological mastery principles in the professional competence of the scientific arbitrator - Argota-Pérez, George (2024)
The aim of the study was to describe methodological mastery principles in the professional competence of the scientific referee. The study was conducted between January and February 2024. Three manuscript evaluation forms corresponding to the guidelines for scientific arbitration from the following journals were selected: Acta Biológica Colombiana, Colombia; Revista Internacional de Contaminación Ambiental, Mexico; and The Biologist (Lima), Peru. Evaluation criteria for each journal were detailed. Additionally, three methodological mastery principles in the professional competence of the scientific referee were described: basic or general, advanced or specific, and complementary. It was highlighted that there were differences and similarities in criteria such as methodological structure and linguistic quality, emphasizing diversity and convergence in review practices. The detailed description of scientific arbitration principles, divided into basic, advanced, and complementary, encompasses ethics, methodology, communication, and quality, enriching the review process. It is argued that diversity in manuscript evaluation is crucial for equitable review. Furthermore, promoting linguistic quality and understanding methodological principles strengthens the integrity of scientific arbitration. It is concluded that the examination of the scientific referee training principles highlights the complexity of manuscript review, from ethical aspects to specific evaluations, emphasizing the importance of integrity and communication for scientific excellence.